From Athens to Vilnius with A Near-Fatal Detour to Minsk? The Issue of Demarcation Between Civil and State Aircraft - Török, Csaba (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
On 23 May 2021, the Belarusian authorities forced a Ryanair flight from Athens to Vilnius to land in Minsk, citing a bomb threat that turned out to be a false alarm. The aircraft was carrying 123 passengers, fortunately none of them were injured in the incident, but one person - a journalist - who had been declared an extremist and persecuted by the Belarusian Government, was immediately detained by the Minsk authorities following the emergency landing. The purpose of this paper is to present the relevant regulatory environment governing the case and, as far as possible, to assess Belarusian behavior in the light of the regulation. However, during the discussion, I will not attempt to judge the case, but rather to highlight the dilemmas surrounding it and similar events like 9/11, such as the problem of the demarcation between civil and state aircraft, the use of weapons against aircraft, the self-defense of states, or the conflict between the human rights of those on board and those on the ground (mainly in the light of the Chicago Convention, the so called San Remo Manual on International Law Applicable to Armed Conflicts at Sea, and the United Nations Charter). „There are only two emotions on a plane: boredom and terror.” (Orson Welles)